2018
DOI: 10.1021/jacs.7b09754
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Regio- and Chemoselective Hydroboration of Pyridines Catalyzed by 1,3,2-Diazaphosphenium Triflate

Abstract: N-Heterocyclic phosphenium triflates (NHP-OTf) 1 serve as efficient catalysts for the regio- and chemoselective hydroboration of pyridines under ambient condition with good functional group tolerance. Mechanistic studies indicate that a boronium salt, [(Py)·Bpin]OTf 4, is generated concomitant with NHP-H 5 via hydride abstraction from HBpin by 1 in the initial reaction step. Hydride reduction of the activated pyridine in [(Py)·Bpin]OTf 4 by NHP-H 5 affords the 1,4-hydroboration product selectively. Thus, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(63 citation statements)
references
References 58 publications
2
59
0
Order By: Relevance
“…The super‐hydricity of 1 a was already confirmed by Gudat et al., who found that 1 a can directly transfer a hydride to aldehydes and diarylketones (within two minutes), and even to alkylketones ( E =−22.30), although rather slowly . The powerfulness of 1 a was also evidenced in other applications such as in catalytic reductions of imines, azocompounds, pyridines, and CO 2 . According to the nucleophilicity parameters disclosed here, 1 a should be roughly 10 2 times more reactive than 1 d ( N =18.74).…”
Section: Figuresupporting
confidence: 73%
“…The super‐hydricity of 1 a was already confirmed by Gudat et al., who found that 1 a can directly transfer a hydride to aldehydes and diarylketones (within two minutes), and even to alkylketones ( E =−22.30), although rather slowly . The powerfulness of 1 a was also evidenced in other applications such as in catalytic reductions of imines, azocompounds, pyridines, and CO 2 . According to the nucleophilicity parameters disclosed here, 1 a should be roughly 10 2 times more reactive than 1 d ( N =18.74).…”
Section: Figuresupporting
confidence: 73%
“…According to Cheng and co‐workers, certain DAPs are among the most nucleophilic hydride donors quantified according to the Mayr nucleophilicity scale . They have been shown to reduce aldehydes and ketones, imines, pyridines, and azobenzenes, as well as α,β‐unsaturated carbonyl derivatives . Kinjo et al.…”
Section: Methodsmentioning
confidence: 99%
“…lato boron cation with at riflate counteranion by the group of Kinjo. [29] Interestingly,t he boron-bonded pyridines in such type of cationic complexes are subjectt or eduction in the presence of hydride sources (i.e.,1 ,4-hydroboration of pyridine). [30] Furthermore, pinacolyl-bound boreniumi ons [LB-Bpin] + were reported to form in solution upon mixing an excess of pinacolborane (HBpin)w ith B(C 6 F 5 ) 3 in the presence of uncharged bases (LB = electronp air donor,t hat is, Lewis base;F igure 7).…”
Section: Three-coordinate Boron(iii) Complexes With One Cationic Charmentioning
confidence: 99%
“…[48] Gessner and co-workers described the boron complex salt 29[PF 6 ]t hat bears two anionic carbon ylidic ligands and which was isolated and characterizedb yX RD analysis( Figure 9). [49] This ligand is marked by af ormally anionic carbon center with two lone pairs and, hence, it resembles an egatively charged version of the non-ionic carbone-typel igand mentioned above.The complex (29 + )w as accessed by hydride abstraction from the bisylide borane (Y 2 BH, Y = anionic ylide) using different salts of trityl cation with aW CA or using B(C 6 F 5 29[HB(C 6 F 5 ) 3 ]) formed highly viscous oils. Therefore, salt metathesis by means of Bu 4 N[PF 6 ]w as employed to craft ac omplex salt which was isolated in analytically pure form.…”
Section: Three-coordinate Boron(iii) Complexes With One Cationic Charmentioning
confidence: 99%